Volatilidade cambial e regimes de câmbio - Bottecchia Filho, Luiz Carlos Tadeu (2011)
Floating exchange rate regimes have been widely adopted since 1973. According to many empirical studies, these regimes have shown greater volatility than fixed exchange rate regimes adopted after the Second World War. However, since the early 1970s, many countries have adopted different types of floating exchange regimes, from freely floating to managed floating, also a wide variety of pegged regimes. The goal of this work is to verify if the exchange volatility is statistically associated to these different types of exchange regimes. Using the de facto exchange rate classification by Reinhart and Rogoff (2004), our research points out that pegged exchange rate regimes are less volatile than freely floating regimes; also, that the exchange rate regime is more volatile in times of monetary instability. A third important result is that commercial and financial openness are not statistically significant.